A hybrid IDM using wavelet transform for a synchronous generator-based RES with zero non-detection zone - Mamun Mishra; Bibhuti Bhusan Pati (AIMS Electronics and Electrical Engineering)
Increased use of renewable energy sources in distribution grids has led to the growing concern over unintentional islanding. Among the available islanding detection methods, the passive methods have larger non-detection zones and are susceptible to system faults. However, they have no effect on power quality like active methods. We present a hybrid method for the islanding detection of synchronous generator-based renewable energy sources. Here, the larger non-detection zone issue of the passive islanding detection method was reduced by combining it with a wavelet transform. The rate of change of a voltage unbalanced factor was computed from the sequence components of the renewable energy source terminal voltage. Then, the factor was analyzed using a wavelet transform, and a threshold for the factor was found. The robustness of the method was tested for several islanding as well as non-islanding situations. The efficacy of the method was also tested in multi-source test systems. From the analysis, it was observed that the proposed method was fast, reliable, and had a zero non-detection zone.